1988
DOI: 10.1021/om00098a001
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of olefins by palladium(II). 11. Kinetics and mechanism of the oxidation of allyl alcohol by PdCl42- in aqueous solution

Abstract: With use of a potentiometric procedure with quinone as reoxidant for Pd(O), the rate expression for allyl alcohol oxidation was determined to be rate = k[PdC1,2-][C6H60]/[H+] [C1-l2, an expression identical in form with that found previously for ethene and other acyclic olefin oxidations indicating similar mechanisms. The two trans attack mechanism suggested for acyclic olefin oxidation involve trans equilibrium hydroxypalladation and external hydroxide ion attack. In regard to the first, with most acyclic ole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 5 publications
4
39
1
1
Order By: Relevance
“…However, the isotope scrambling experiments with allyl-1,1-d2 15 alcohol indicates that hydroxypalladation is not an equilibrium step. 18 As discussed before, earlier theoretical calculations6…”
Section: General Overview On Dynamic Calculationsmentioning
confidence: 79%
See 2 more Smart Citations
“…However, the isotope scrambling experiments with allyl-1,1-d2 15 alcohol indicates that hydroxypalladation is not an equilibrium step. 18 As discussed before, earlier theoretical calculations6…”
Section: General Overview On Dynamic Calculationsmentioning
confidence: 79%
“…4). 18 The isomerisation between H 2 C=CHCD 2 OH and D 2 C=CHCH 2 OH was indeed not observed (Scheme 5). The lack of isotopic scrambling indicated that the nucleophilic addition is not an equilibrium process.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…This species of palladium (II) in the presence of chloride has also been observed earlier. 15 The complex between the active form of the catalyst, PdCl , and the substrate, allyl alcohol, is a type of p-complex 16 which may be of the form.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms of catalysis to some extent is complicated by the formation of different intermediate complexes, free radicals and different oxidation states [16,17]. Palladium (II) chloride (Pd(II)) has been used as a catalyst in the oxidation of several substrates in alkaline medium and some of them have been proved to be suitable for kinetic analysis [11,[18][19][20][21][22]. This background instigated us to carry out the detailed study on the kinetics and mechanism of NTT-CAT redox system in alkaline medium with and without Pd(II) catalyst.…”
Section: Introductionmentioning
confidence: 99%